Analisis nilai-nilai pendidikan lingkungan dalam materi PABP tingkat SMP kelas VII di sekolah perspektif Al Qur'an - Arif Afandi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2022)
AbstractIslamic Religion Education exixts to instill moral and religios value for students in the school to love and protect their environment both at school and out of school. This requires iwlqmic religion education subjects have a considerable so that PAI subjects can be integrated into environment. This study use qualitative approach with the type of library research. Data collection technique by reading and analyzing student text book for seventh grade PABP subject KI and KD in PABP subject and can be supported by other documents. Analysis of thw value of environmental education in seventh grade PABP subject is in chapter 1 on closer to God SWT whose name is very beautiful, chapter 3 on everything is clean so becomes comfortable and chapter 4 on the beauty of togetherness with congregational prayers.Keywords : Education, Environment, Subject